2018
DOI: 10.1002/adma.201706407
|View full text |Cite
|
Sign up to set email alerts
|

Lipase‐Triggered Water‐Responsive “Pandora's Box” for Cancer Therapy: Toward Induced Neighboring Effect and Enhanced Drug Penetration

Abstract: Insufficient drug release as well as poor drug penetration are major obstacles for effective nanoparticles (NPs)-based cancer therapy. Herein, the high aqueous instability of amorphous calcium carbonate (ACC) is employed to construct doxorubicin (DOX) preloaded and monostearin (MS) coated "Pandora's box" (MS/ACC-DOX) NPs for lipase-triggered water-responsive drug release in lipase-overexpressed tumor tissue to induce a neighboring effect and enhance drug penetration. MS as a solid lipid can prevent potential d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
118
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 138 publications
(120 citation statements)
references
References 41 publications
2
118
0
Order By: Relevance
“…We recently explored nanosized amorphous calcium carbonate (ACC), which can be more readily obtained by various simple methods, unlike crystallized calcium carbonate (CCC) that is usually in the micrometer range of size. The high aqueous instability of ACC, which is responsible for its quick drug release in aqueous medium, has generally been recognized as the major obstacle for employing ACC as a DDSs.…”
Section: Introductionmentioning
confidence: 99%
“…We recently explored nanosized amorphous calcium carbonate (ACC), which can be more readily obtained by various simple methods, unlike crystallized calcium carbonate (CCC) that is usually in the micrometer range of size. The high aqueous instability of ACC, which is responsible for its quick drug release in aqueous medium, has generally been recognized as the major obstacle for employing ACC as a DDSs.…”
Section: Introductionmentioning
confidence: 99%
“…Drug delivery systems (DDS) based on nanoparticles have been demonstrated to exert enhanced bioavailability while at the same time can greatly reduce undesired side effects as compared to free drugs, which has been well recognized as a promising alternative for effective cancer therapy [1][2][3]. Therefore, different kinds of DDSs based on various materials (varying from organic to inorganic ones) have been explored [1,[4][5][6]. Silica nanoparticles (SLN) as one of the most widely adopted material is emerging as a promising candidate due to its versatile merits [7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…The competitive uptake assay strongly suggested that the surface-anchored HA was involved in the variations of cellular uptake between different formulations, which suggested that HA modification might be able to guide the DDS to the CD44 receptor overexpressed cells with high affinity for the same molecule. 30 The in vivo targeting assay in the current study clearly demonstrated that the tumour targeting nature of HA could guide the HM to accumulate in the in vivo tumour tissue. 31,32 Moreover, the in vivo antitumour assay further confirmed the enhanced anticancer benefits of Dox and Que in the current study.…”
Section: Discussionmentioning
confidence: 54%